2022
DOI: 10.1155/2022/1427110
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3 Mitigates Oxidative Stress-Induced Damage to Nucleus Pulposus-Derived Mesenchymal Stem Cells through PI3K/Akt Pathway

Abstract: Intervertebral disc degeneration (IVDD) is one of the main causes of low back pain. The local environment of the degenerated intervertebral disc (IVD) increases oxidative stress and apoptosis of endogenous nucleus pulposus-derived mesenchymal stem cells (NPMSCs) and weakens its ability of endogenous repair ability in degenerated IVDs. A suitable concentration of 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3) has been certified to reduce oxidative stress and cell apoptosis. The current study investigated the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Therefore, some studies began to focus on how to make stem cells withstand the damage of local oxidative stress. Studies have shown that some medicine like cyclosporine A and 1,25(OH) 2 D 3 can alleviate the apoptosis of MSC caused by oxidative stress and promote the survival of MSC [ 116 , 117 ]. At present, the abovementioned natural origin, chemical medicine, biomaterials, and stem cell therapy are still in the stage of cell and animal experiments.…”
Section: Therapy Target For Oxidative Stress-related Iddmentioning
confidence: 99%
“…Therefore, some studies began to focus on how to make stem cells withstand the damage of local oxidative stress. Studies have shown that some medicine like cyclosporine A and 1,25(OH) 2 D 3 can alleviate the apoptosis of MSC caused by oxidative stress and promote the survival of MSC [ 116 , 117 ]. At present, the abovementioned natural origin, chemical medicine, biomaterials, and stem cell therapy are still in the stage of cell and animal experiments.…”
Section: Therapy Target For Oxidative Stress-related Iddmentioning
confidence: 99%
“…Although numerous medicines and updated surgical techniques have been applied to solve this issue, the clinical effects remain unsatisfactory because they can only relieve symptoms without directly controlling IVDD. 26,27 Oxidative stress has been proven to participate in NPC apoptosis, which promotes the process of IVDD. 12,28 TBHP is superior to H 2 O 2 as an exogenous inducer of oxidative stress because of its high stability and slow-release capability.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying IVDD remain complicated and not fully understood. Although numerous medicines and updated surgical techniques have been applied to solve this issue, the clinical effects remain unsatisfactory because they can only relieve symptoms without directly controlling IVDD 26,27 . Oxidative stress has been proven to participate in NPC apoptosis, which promotes the process of IVDD 12,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhou XP had the most co-authorship strength (total link strength = 87), with 17 documents and 348 citations [28], followed by Liang CZ (total link strength = 85) with 16 documents and 392 citations [29] and Li FC (total link strength = 84) with 16 documents and 358 citations [30] (Figure 3(a)). Moreover, the closest collaboration organization was Shanghai Jiao Tong University (total link strength = 20) with 15 documents and 290 citations, the second organization was Yangzhou University (total link strength = 18) with 13 documents and 224 citations, and the third was Chinese Orthopaedic Regenerative Medicine Society (total link strength = 14) with 6 documents and 239 citations [31][32][33] (Figure 3(b)). Besides, the strongest collaborative country was the USA (total link strength = 58) with 94 documents and 4791 citations, followed by China (total link strength = 35) with 231 documents and 4522 citations and Japan (total link strength = 24) with 30 documents and 2612 citations (Figure 3(c)).…”
Section: Contribution Of Authors Organizations and Countriesmentioning
confidence: 99%